Acidosis increases the susceptibility of respiratory epithelial cells to Pseudomonas aeruginosa-induced cytotoxicity - Torres, Iviana M. (Am J Physiol Lung Cell Mol Physiol, 2017)
Bacterial infection can lead to acidosis of the local microenvironment, which is believed to exacerbate disease pathogenesis; however, the mechanisms by which changes in pH alter disease progression are poorly understood. We test the hypothesis that acidosis enhances respiratory epithelial cell death in response to infection with Pseudomonas aeruginosa. Our findings support the idea that acidosis in the context of P. aeruginosa infection results in increased epithelial cell cytotoxicity due to ExoU intoxication. Importantly, enforced maintenance of neutral pH during P. aeruginosa infection demonstrates that cytotoxicity is dependent on the acidosis. Investigation of the underlying mechanisms revealed that host cell cytotoxicity correlated with increased bacterial survival during an acidic infection that was due to reduced bactericidal activity of host-derived antimicrobial peptides. These findings extend previous reports that the activities of antimicrobial peptides are pH-dependent and provide novel insights into the consequences of acidosis on infection-derived pathology. Therefore, this report provides the first evidence that physiological levels of acidosis increase the susceptibility of epithelial cells to acute Pseudomonas infection and demonstrates the benefit of maintaining pH homeostasis during a bacterial infection.